Better forbearance, lower depression: Evidence based on heart rate variability - Su, Tiehong; Guo, Xinwen; Liu, Manhua; Xiao, Rong; Xiao, Zhongju (Frontiers in Psychology, 2023)
Background The relationship between forbearance, a psychological resource, and depression has to date remained inconclusive. The present study investigated heart rate variability (HRV) reactivity to acute stressor tasks in participants with different levels of forbearance to discover how forbearance influences depressive emotions when facing adversity. Method The study examined the relationship between forbearance and depression, comparing HRV reactivity to stressor tasks in participants with different levels of forbearance. The levels of reported forbearance were assessed by the Forbearance Scale (FS). The Patient Health Questionnaire-9 (PHQ-9) was used to assessed depression severity. HRV reactivity was evaluated at five stages: baseline, the active stressor task, the period of recovery after the active stressor task, the passive stressor task, the period of recovery after the passive stressor task. Results FS scores had a significant negative correlation with PHQ-9 and a significant positive correlation with HRV; significant differences existed between the basal HRV in the higher and lower FS groups. In the passive stressor task and the period of recovery after the active stressor task, significantly different HRV responses were identified between the two groups. Discussion Forbearance was correlated with depression and HRV. The present research found differences in HRV among subjects with different levels of forbearance in the baseline as well as stressor and recovery periods, suggesting that self-regulation dysfunction may exist among persons with lower levels of forbearance. Because of the higher levels of forbearance, the negative emotions of individuals caused by adversity are mitigated.